MENTAL WORKLOAD OF ELECTRICAL WORKSHOP PERSONNEL AS CONSIDERATIONS FOR EVALUATION OF FASHARKAN SURABAYA PERSONNEL NEEDS BASED ON COMPETENCE - Joko Setiaji; Budisantoso Wirjodirjo; Eko Krisdiono (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
The Indonesian National Army (TNI) in general and the Navy in particular as a national defense tool, according to the government's program, has taken policies, one of which is the Modernization of the KRI. This policy demands balance from the point of view of the KRI maintenance system. Maintenance and repair facilities in Surabaya are based on Kep Kasal Number kep/1059/2016 concerning the Instruction Manual for Ship Platform Material Development within the Indonesian Navy (PU-7.08) regarding the duties and authorities of Fasharkan as an agency and unit for providing maintenance assistance in the field of platforms. The electrical workshop is one of the elements that need to be prepared to welcome the KRI modernization program at the Indonesian Armada II Command Headquarters. In line with the results of the maintenance and repair processes that have not been maximized, it is necessary to measure the physical and mental workload of all electrical workshop personnel so that they are able to solve the problems faced. The measurement results show that technology and personnel factors according to the needs of KRI maintenance are dominant in influencing excessive workload. Physical measurement results require the addition of 1 (one) personnel for each type of job position. Using the NASA TLX approach method produces mental indicators In line with the results of the maintenance and repair processes that have not been maximized, it is necessary to measure the physical and mental workload of all electrical workshop personnel so that they are able to solve the problems faced. Keywords: Electrical Workshop, workload factor, Nasa TLX